2011
DOI: 10.1038/ejcn.2011.142
|View full text |Cite
|
Sign up to set email alerts
|

Acute differential effects of milk-derived dietary proteins on postprandial lipaemia in obese non-diabetic subjects

Abstract: Background/Objectives: Postprandial lipaemia is an established risk factor for atherosclerosis. To investigate the acute effect of four milk-derived dietary proteins (alpha-lactalbumin, whey isolate, caseinoglycomacropeptide and whey hydrolysate) on postprandial lipaemia, we have conducted a randomized, acute, single-blinded clinical intervention study with crossover design. Subjects/Methods: A total of 11 obese non-diabetic subjects (age: 44-74, BMI: 30-41.4 kg m -2 ) were included. On 4 different days the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 38 publications
(41 reference statements)
1
23
0
Order By: Relevance
“…Protein from cow milk is made up of w20% whey and w80% casein (20), and it is the whey portion that is thought to be responsible for the insulinotropic effect (32). Holmer-Jensen et al (33) showed that consumption of a high-fat test meal that contained 45 g whey hydrolysate raised the 30-min insulin response compared with the effect of consumption of 3 other meals with different sources of milk-derived proteins as follows: a-lactalbumin, whey isolate, and caseinoglycomacropeptide. Although these 4 meals were isoenergetic and equal in macronutrient profiles, they were much higher in total energy and fat contents than in the current study (w4980 compared with w2090 kJ, respectively, and 66% energy from fat compared with 36%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Protein from cow milk is made up of w20% whey and w80% casein (20), and it is the whey portion that is thought to be responsible for the insulinotropic effect (32). Holmer-Jensen et al (33) showed that consumption of a high-fat test meal that contained 45 g whey hydrolysate raised the 30-min insulin response compared with the effect of consumption of 3 other meals with different sources of milk-derived proteins as follows: a-lactalbumin, whey isolate, and caseinoglycomacropeptide. Although these 4 meals were isoenergetic and equal in macronutrient profiles, they were much higher in total energy and fat contents than in the current study (w4980 compared with w2090 kJ, respectively, and 66% energy from fat compared with 36%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Milk proteins have been extensively investigated for their insulinotropic and glucose-lowering effects in healthy subjects (73,75,82,83,(90)(91)(92)(93)(94)(95)(96)(97)(98)(99) and to a limited extent in individuals with suboptimal glucose control (100)(101)(102)(103)(104)(105)(106) . The dose varied significantly between studies from as little as 10 g (92,105,106) -51 g (91) .…”
Section: Short-term Studies On Glycaemic Controlmentioning
confidence: 99%
“…In acute studies, postprandial triglyceride (TG) responses measured as iAUC decreased significantly in both obese non-diabetic subjects [39] and T2D subjects [40] after consumption of WPI in comparison with other dietary protein sources (cod, casein or gluten) or glucose. In contrast, no difference in postprandial TG responses was observed when the acute effects of WPI and WP-specific fractions in obese, non-diabetics [47] and T2D subjects [46] were compared. Furthermore, studies comparing WP to other dietary protein sources found a sup- pression of the response to free fatty acids (FFA) [39,40].…”
Section: Lipid Metabolismmentioning
confidence: 88%
“…Other studies that investigated the GLP-1-stimulating effect of WP in healthy [32,38] and T2D subjects [27,40,46] did not detect any changes in the GLP-1 responses when expressed as incremental area under the curve (iAUC). Also, no difference was found in obese, non-diabetic subjects between WPI and WPspecific fractions (WPH and WP enhanced with α-lactalbumin and caseinoglycomacropeptide, respectively) [47]. The incretin results are summarized in Table 1.…”
Section: Glucose Metabolismmentioning
confidence: 88%
See 1 more Smart Citation